Self-Regulated Online Learning of Rural University EFL Students - Mudra, Heri (STAIN Sultan Abdurrahman Kepulauan Riau, 2025)
It is undisputable that learning English through an online course remains challenging for most rural university learners. This study was focused on determining various self-regulation strategies during an online course employed by EFL learners from several universities located in rural areas. A total of 137 learners in 1st, 3rd, 5th, and 7th semesters voluntarily participated in the online survey study for several weeks. The results revealed that there were several general strategies applied by the learners, including metacognitive skills, time management, environmental structuring, persistence, and help seeking strategies. Among them were time management and environmental structuring strategies which reduce the improvement learners’ self-regulation. In short, self-regulated learning is much influenced by learners’ attitude and competence to integrate technology into online course that is mostly new in the rural context.